ANALISIS PENERAPAN AKUNTANSI BIAYA LINGKUNGAN PADA RUMAH SAKIT ISLAM SAMARINDA - Camelia Verahastuti, Febry Setiawan, Titin Ruliana, (EKONOMIA, 2020)
Any organization or company that produces products or services as outputs of its operations automatically has responsibility for the environment around the company in waste management. The largest waste is produced by the hospital unit. Hospital waste is a hazardous waste for environmental safety if it is not managed first before disposal.The purpose of this study is to know and analyze how firms identify, acknowledge, measure, and present and disclose environmental costs in their financial statements.The related analysis of the environmental accounting treatment stages based on environmental cost sharing according to Hansen & Mowen (2007) and the Financial Statement Preparation Framework (2015).Based on the results of the analysis it can be concluded that the House Sakir Islam Samarinda not do the treatment of environmental cost accounting. The environmental costs report is compiled on the balance sheet and profit and loss statement.